Waste to energy: Facile, low-cost and environment-friendly triboelectric nanogenerators using recycled plastic and electronic wastes for self-powered portable electronics - Muhammad Umaid Bukhari (17148322) (2022)
Human are producing plastic and electronic wastes in huge amount, polluting our environment especially water resources and causing life-threatening complications. On the other hand, the increasing consumption of fossil energy is further damaging our environment. To help mitigate these problems, we present a facile, environment-friendly, and low-cost triboelectric nanogenerator (TENG) by recycling plastic and electronic waste for power generation through biomechanical energy. The proposed graphite and plastic based triboelectric nanogenerator (GP-TENG) is fabricated by recycling the electronic waste (dry cells) to get graphite and the plastic bottles to get plastic. GP-TENG is fabricated by low-cost, facile, and environment-friendly in-house rapid fabrication process which is solvent- and cleanroom-free and doesn’t require specialized equipment and expertise. The output performance of the GP-TENG is systematically studied with an open-circuit voltage of 83.88 V, short circuit current of 101 µA, and maximum output power density of 26.54 µW/cm2 . To demonstrate its practical applications, a digital calculator, an electronic watch, and nineteen blue light-emitting diodes (LEDs) were powered using GP-TENG. Our approach generates renewable energy by recycling plastics and electronic wastes, and therefore it provides a sustainable and viable path towards the vision of building a green world. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2021.12.072